Acrylamide in food : analysis, content and potential health effects - Gökmen, Vural (Elsevier, 2016)
Acrylamide in Food: Analysis, Content and Potential Health Effects provides the recent analytical methodologies for acrylamide detection, up-to-date information about its occurrence in various foods (such as bakery products, fried potato products, coffee, battered products, water, table olives etc.), and its interaction mechanisms and health effects. The book is designed for food scientists, technologists, toxicologists, and food industry workers, providing an invaluable industrial reference book that is also ideal for academic libraries that cover the domains of food production or food s.